Timing and intensity of weed harrowing in spring barley - Piotr Sobkowicz; Ewa Tendziagolska; Grzegorz Cwanek; Bartłomiej Dróżdż; Joanna Gisman; Aneta Hawryluk (Agricultural and Food Science)
At present weed harrowing is gaining significance in conventional agriculture as there is a growing trend to reduce the application of pesticides. Unfortunately, the harrowing is partially damaging to crop plants. The objective of the study was to find the optimum timing and intensity (1–3 harrow passes) of weed harrowing in spring barley. A 3-year one-factor field experiment was conducted on the alluvial loamy sand soil. Weed harrowing was conducted at different growth stages of barley. The additional treatments were: the increased seeding rate of barley by 20%; herbicide application and an untreated control. At least two passes with spring-tine harrow: at barley emergence and next at tillering or at the 2-leaf stage and tillering were needed for the significant weed density reduction, but only the first treatment did not reduce barley grain yield. Three harrow passes: at barley emergence, the 2-leaf stage, and tillering most efficiently reduced weed density but were also most damaging to barley. The experiment showed that when planning weed harrowing twice during barley growth, the cereal needs a long period of time to recover after the first cultivation.